EFL Students’ Memory Strategies in Writing Essay - Ayu, Habsa; Pehala, Ilfan Askul (IAIN KENDARI, 2022)
The purpose of this study was to determine the application of EFL students' memory strategies when writing essays. This study uses qualitative methods to collect data through reflection as a research instrument. The results of the study revealed that students used different memory strategies to help make it easier for them to write essays. The memory strategy that many students use when writing reads the references related to the essay topic they are going to write. Having many references makes it easier for students to develop their ideas, student writing is more varied, and it is easier for students to write essays. Memory strategy has an influence on students' essay writing.Keywords: Essay writing; memory strategy; writing essay.